Mechanical valve replacement in adults with Fontan physiology is an effective palliation in selected patients - Moustafa, Amr; Abdelhalim, Ahmed T.; Miranda, William R.; Connolly, Heidi M.; Stephens, Elizabeth H.; Dearani, Joseph A.; Egbe, Alexander C. (International journal of cardiology congenital heart disease, 2025)
Valve regurgitation is associated with systemic ventricular dysfunction and mortality in patients with Fontan palliation. Valve repair and valve replacement with bioprostheses have limited durability, and outcomes after valve replacement with mechanical prostheses are poorly defined. The study objectives were to assess: (1) Operative mortality, valve-related complications (stroke, mechanical valve thrombosis, major bleeding complication, prosthetic valve endocarditis, and valve reoperation), and late mortality/transplant. (2) Postoperative changes in ventricular volumes and ejection fraction; (3) Postoperative changes in the clinical indices of disease severity. Retrospective cohort study of adults (age ≥18 years) with Fontan palliation who underwent isolated aortic or atrioventricular valve replacement at Mayo Clinic (2003–2023). Preoperative and postoperative evaluations (clinical evaluation, echocardiogram, biomarkers) were performed 6 months preoperatively and 6–24 months postoperatively, respectively. Overall, 17 patients underwent isolated atrioventricular (N = 9) or aortic valve (N = 8) replacement with mechanical prosthesis (age 27 ± 8 years; 9 [53 %] males). There was no operative mortality. There was postoperative improvement in functional capacity (NYHA class), heart failure indices (NT proBNP), and hepatorenal function (MELD-XI score). There was a postoperative decrease in systemic ventricular volumes, without change in ejection fraction. The 10-year cumulative incidence of valve-related complications and death/transplant was 15 % and 18 %, respectively. Atrioventricular valve and aortic valve replacement with mechanical prostheses was associated with low (zero) operative mortality, low risk of valve-related complications, and clinical improvement. This suggests that valve replacement with mechanical prostheses may be an effective palliation in selected patients and may delay the need for transplant in this population.